MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS VIII B SMPN 3 PARINGIN PADA MATERI SISTEM GERAK MANUSIA MENGGUNAKAN PENDEKATAN WHOLE BRAIN TEACHING (WBT) MELALUI METODE EKSPERIMEN - Khairunnisa Khairunnisa (Universitas Lambung Mangkurat, 2014)
Abstract. Research on improving students' science process skills through an approach Whole Brain Teaching (WBT) on the material motion system in humans through the experimental method. WBT approach application through the experimental method is expected to have a positive impact on the construction of students 'knowledge and science process skills of students in the learning process, especially in the materials science of human motion system so as to improve students' understanding of the material. This study aims to determine the improvement of students' science process skills using WBT approach through experimental methods in material of human motion system. The method used was classroom action research which consists of planning, action, observation, and reflection. This research was conducted at SMP Negeri 3 Paringin in class VIII B comprised 18 students in the first semester of the school year 2013/2014. This classroom action research was conducted in two cycles, each cycle consisting of three meetings. Data collected by the observation sheet science process skills and achievement test. Qualitative data analysis techniques based on descriptive analysis of the increase from cycle to cycle two. The study concluded that: (1) The student process skills of students increased from lower to higher category. (2) the results of student learning increased from 44.44% to 88.89%. Thus the application of WBT approach can improve students' science process skills.Keywords: Whole Brain Teaching, human motion system, Experiment.